Variasi Bahasa Dalam Film “Yowis Ben: Finale” Karya Bayu Skak (Kajian Sosiolinguistik) - Niko Dharmawan; Udjang Pairin Basir (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
In social life, language is very much needed as a means of social communication between one human being and another. The language used in society has a variety of languages, such as the language used in the film "Yowis Ben: Finale" by Bayu Skak. In the film, the characters use Javanese with very diverse dialects. However, there are also conversations with other language codes, namely Indonesian as a form of code switching and code mixing. From the explanation above regarding the background, this research uses sociolinguistic studies. Furthermore, the formulation of the problem in this research is the form of dialect variation in the film "Yowis Ben: Finale", the form of code switching in the film "Yowis Ben: Finale", and the form of code mixing in the film "Yowis Ben: Finale". This research uses a qualitative descriptive method which is expected to explain the data found objectively. The data sources for this research are words, phrases, clauses and sentences in conversations between characters in the film. Then, the techniques used to collect data are documentation techniques in the form of bush techniques and note-taking techniques. The results of the research in the film "Yowis Ben: Finale" are (1) the form of dialect variations, (2) internal code switching, and (3) external code switching, (4) positive code mixing, and (5) negative code mixing.